2021
DOI: 10.1172/jci.insight.153732
|View full text |Cite
|
Sign up to set email alerts
|

Differential importance of endothelial and hematopoietic cell GLP-1Rs for cardiometabolic versus hepatic actions of semaglutide

Abstract: Glucagon-like peptide-1 receptor agonists (GLP-1RA) are used to treat diabetes and obesity and reduce rates of major cardiovascular events such as stroke and myocardial infarction.Nevertheless, the identity of GLP-1R-expressing cell types mediating the cardiovascular benefits of GLP-1RA remains incompletely characterized. Herein, we investigated the importance of murine Glp1r expression within endothelial and hematopoietic cells. Mice with targeted inactivation of the Glp1r in Tie2+ cells exhibited reduced lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 52 publications
2
20
0
Order By: Relevance
“…Recent observations made by McLean et al. 123 also indicated that functions of GLP-1RAs in extra-pancreatic organs could be attributed to GLP-1R expressed in endothelial and hematopoietic cell lineages, in agreement with the detection of GLP-1R in smooth muscle cells in the walls of arteries and arterioles of monkey and human lungs 118 .…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Recent observations made by McLean et al. 123 also indicated that functions of GLP-1RAs in extra-pancreatic organs could be attributed to GLP-1R expressed in endothelial and hematopoietic cell lineages, in agreement with the detection of GLP-1R in smooth muscle cells in the walls of arteries and arterioles of monkey and human lungs 118 .…”
Section: Discussionsupporting
confidence: 71%
“…Thus, it remains to be determined whether GLP-1RAs exert their anti-inflammatory and immune-modulatory functions via indirect mechanisms. This could involve a brain–peripheral tissue axis, or via interaction with a small population of immune cells, such as intestinal intraepithelial lymphocytes (IEL) or certain T lymphocytes ( γδ cells) 123 , 182 . Recent observations made by McLean et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Glucagon-like peptide-1 (GLP-1) is a gut-derived incretin hormone that inhibits glucagon secretion and can lead to weight loss with prolonged use. 8 , 9 These mechanisms of action support the clinical development of anti-degradative glucagon-like peptide-1 receptor agonists (GLP-1RA) for the obesity, which was associated with type 2 diabetes mellitus, non-alcoholic fatty liver disease, and cardiovascular disease. 10 , 11 Although there is evidence that GLP-1RA can reduce body weight, however, this weight loss may not be entirely attributable to fat mass, estimated to be approximately 25–33% including a reduction in lean body mass (LBM).…”
Section: Introductionmentioning
confidence: 96%